2017
DOI: 10.1177/1753944717711138
|View full text |Cite
|
Sign up to set email alerts
|

Taurine supplementation has anti-atherogenic and anti-inflammatory effects before and after incremental exercise in heart failure

Abstract: our results suggest that 2 weeks of oral taurine supplementation increases the taurine levels and has anti-atherogenic and anti-inflammatory effects prior to and following incremental exercise in HF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 28 publications
1
21
0
2
Order By: Relevance
“…Further clinical studies demonstrated that patients with type-2 diabetes following supplementation of taurine (500 mg/3 times/day for 2 weeks) also attenuated vascular dysfunction assessed by lower FMD (flow-mediated dilatation), indicating that taurine alone reverses endothelial dysfunction, which is the primary path to atherosclerosis. However, the other CVD parameters, such as heart rate, ejection rate, or inflammation (detected by hsCRP), were not found in these patients [215], unlike those with heart failure [207]. Supplementing type-2 diabetic patients with 1500 mg/day taurine for 90 days was shown to lower arachidonic acid levels compared to control subjects.…”
Section: Taurine As a Therapeutic In Cardiovascular Disease: Human CLmentioning
confidence: 74%
See 2 more Smart Citations
“…Further clinical studies demonstrated that patients with type-2 diabetes following supplementation of taurine (500 mg/3 times/day for 2 weeks) also attenuated vascular dysfunction assessed by lower FMD (flow-mediated dilatation), indicating that taurine alone reverses endothelial dysfunction, which is the primary path to atherosclerosis. However, the other CVD parameters, such as heart rate, ejection rate, or inflammation (detected by hsCRP), were not found in these patients [215], unlike those with heart failure [207]. Supplementing type-2 diabetic patients with 1500 mg/day taurine for 90 days was shown to lower arachidonic acid levels compared to control subjects.…”
Section: Taurine As a Therapeutic In Cardiovascular Disease: Human CLmentioning
confidence: 74%
“…In fact, exercise in HF patients has been shown to improve circulating angiogenic cells [206]. In addition, taurine supplementation (500 mg/3 times/day for 2 weeks) in patients with HF significantly reduced total cholesterol, triglyceride levels, high-density lipoprotein cholesterol, and inflammatory biomarker hsCRP (high sensitivity C reactive protein) levels, both prior to and after exercise [207]. This suggests that taurine supplementation may exert a beneficial impact on the cardiovascular system in patients with CVD complications.…”
Section: Taurine As a Therapeutic In Cardiovascular Disease: Human CLmentioning
confidence: 99%
See 1 more Smart Citation
“…In a human study that included smokers, it was found that Tau was positively associated with endothelial functioning ( 206 ). Recently, it was shown that Tau exerts anti-atherogenic as well as anti-inflammatory effects (lowering of C-reactive protein (CRP) and platelets) in patients with HF and a left ventricular ejection fraction of <50% ( 207 ). Tau and Mg supplementation significantly increased the endothelial progenitor cell (EPC) colony numbers (EPCs repair endothelial damage to prevent CVDs) and significantly decreased free radical levels and thiobarbituric acid scores in healthy men.…”
Section: Conditionally Essential Aas In Atherosclerosismentioning
confidence: 99%
“…As a potential pharmacological agent, its role against oxidative stress and inflammation has been investigated by different studies. It protects against various diseases and disorders in different organ systems such as the integumentary, cardiovascular, respiratory, muscular, skeletal, circulatory and endocrine systems [[6], [7], [8], [9], [10], [11], [12]].…”
Section: Introductionmentioning
confidence: 99%